On dispersing representations of quivers and their connection with representations of bundles of semichains - Bondarenko, V.M. (Algebra and Discrete Mathematics, 2002)
In the paper we discuss the notion of “dispersing representation of a quiver” and give, in a natural special case, a criterion for the problem of classifying such representations to be tame. In proving the criterion we essentially use representations of bundles of semichains, introduced about fifteen years ago by the author.